If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + z + 2 = 2 Reorder the terms: 4 + 2 + z = 2 Combine like terms: 4 + 2 = 6 6 + z = 2 Solving 6 + z = 2 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + z = 2 + -6 Combine like terms: 6 + -6 = 0 0 + z = 2 + -6 z = 2 + -6 Combine like terms: 2 + -6 = -4 z = -4 Simplifying z = -4
| 3x+6py-7=0 | | y-11=-10 | | (5p^3)(-m^8p^2)= | | -5x+17=-20x-18 | | p=s-14 | | 36x+200=76x | | x-11=5x | | 12x-4=96x-12 | | y=3x+-8 | | 4(x-y)(x-y)-25= | | 26x+9=8x+39 | | b+10=-13 | | 8=vu | | 3a-3=4a-1.5 | | x^2-18=19 | | (9-y)(4y+6)=0 | | 17+26x=30 | | -2x^2-x-3=0 | | 14-t=-10 | | 8.26x+4=68.2276+2x | | y=-.2x+12 | | 14.95-7.55= | | 13-k=5 | | 3/4x-7/4=8 | | 14r+12r=832 | | 9x+2=27x | | 5.7(x-1)=-0.3+42.3 | | -3y-2=-2y | | -7x^3*8x^2= | | 9x^2+24x=9 | | 5m^2=112+8m | | p^2+3p^3-3p-1=0 |